Superovulation with a high gonadotropin dose for in vitro fertilization: Is it effective? - Lashen, Hany (Springer US, 1998)
PURPOSE: Our purpose was to investigate the effect on the ovarian response of increasing the gonadotropin dose. METHODS: We analyzed retrospectively the in vitro fertilization data for patients who had two cycles of treatment, with a higher dose in cycle 2. The patients were stratified according to age, ovarian response, and gonadotropin dose in the first cycle. The main outcome measure was the number of follicles, eggs, and embryos and the peak estradiol (E(2)) level. RESULTS: The study included 244 patients. Patients in both age groups (n = 118, - <33 years; n = 126, > 33 years), low (n = 66) and intermediate (n = 145) responders, and patients who received < 225 IU folliclestimulating hormone (n = 175) in cycle I had a better response in cycle 2. However, the high responders (n = 33) and those who received 225 or 300 IU folliclestimulating hormone (n = 69) in cycle I showed a similar response in both cycles, except for a significantly higher E(2) level in cycle 2. CONCLUSIONS: Our results indicate that exceeding a daily dose of 300 IU is unrewarding.